Inelastic response of silicon to shock compression. - Higginbotham, A; Stubley, P; Comley, A; Eggert, J; Foster, J; Kalantar, D; McGonegle, D; Patel, S; Peacock, L; Rothman, S; Smith, R; Suggit, M; et al. (Nature Publishing Group, 2016)
The elastic and inelastic response of [001] oriented silicon to laser compression has been a topic of considerable discussion for well over a decade, yet there has been little progress in understanding the basic behaviour of this apparently simple material. We present experimental x-ray diffraction data showing complex elastic strain profiles in laser compressed samples on nanosecond timescales. We also present molecular dynamics and elasticity code modelling which suggests that a pressure induced phase transition is the cause of the previously reported 'anomalous' elastic waves. Moreover, this interpretation allows for measurement of the kinetic timescales for transition. This model is also discussed in the wider context of reported deformation of silicon to rapid compression in the literature.